Pengaruh Model Pembelajaran ASSURE TERHADAP Hasil Belajar Siswa pada Materi Suhu dan Kalor - Sunartih Sunartih; Marungkil Pasaribu; Amiruddin Hatibe (Faculty of Teacher Training and Education, Musamus University, 2018)
This study aims to determine whether there is an influence of ASSURE learning model on student learning outcomes in temperature and heat material of class XI SMA. The method used is quasi-experimental with equivalent pretest-posttest design. The population of this study were all students of class XI SMA . Sampling was carried out by purposive sampling with the sample of the study being class XI Mipa 2 as the experimental class and class X1 Mipa 5 as the control class. The research instrument in the form of learning outcomes tests and observation sheets that have been validated by the validator and field tested. Data analysis used inferential statistics is normality, homogeneity, hypothesis testing (2-party t test). Based on the results of research and analysis of research data, obtained the value of student learning outcomes at posttest average value of the experimental class is 14.90 with a standard deviation of 3.23 and for the control class of 11.57 with a standard deviation of 2.99. The test results of the t test statistic of 2 parties from hypothesis testing obtained the price thitung(4,11)>ttabel(1,67) or thitung(-4,11)>ttabel(-1,67) so that H1 is accepted and H0 is rejected. This result states that there are differences in student learning outcomes in physics subjects between classes taught with the ASSURE learning model and Direct Intruction learning models. It can be concluded that there is an influence of the ASSURE learning model on student learning outcomes in temperature and heat material in class XI of SMA. Keywords: assure learning model, learning outcomes, temperature and heat